The Progress of Paperless Trade in Asia and the Pacific: Enabling International Supply Chain Integration - Sung Heun Ha; Sang Won Lim (Asian Development Bank (ADB), 2014)
This paper discusses on how to facilitate paperless trade for international supply chain integration in the Asia and Pacific region. The paper defines paperless trade and describes how paperless trade can improve efficiency of international supply chain, including its economic benefits. Based on the review of paperless trade initiatives and assessment of paperless trade readiness of countries in the Asia and Pacific region, the paper identifies five critical challenges in facilitating cross-border paperless trade: use of common international standards, harmonization of different legal frameworks, capacity gaps among the parties, cooperation between the public and private sectors, and lack of coordination mechanisms for cross-border data exchanges. For each challenge, the paper describes its nature and possible measures for alleviating it. In its annexes, the paper also provides implementation cases of cross-border paperless trade in the Asia and Pacific region, namely Pan Asian e-Commerce Alliance (PAA) and electronic Certificate of Origin between the Republic of Korea and Taipei,China.
hdl:11540/2269
Keywords: F15; F19; 330; Paperless trade; international supply chain integration; trade facilitation